2014
DOI: 10.7241/ourd.20141.01
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid abuse on the face: a prospective, study on outpatients of dermatology

Abstract: Introduction: Topical corticosteroids (TCS) are widely misused. Uncontrolled use of steroids can cause undesirable adverse effects especially on face. Aim: The aim of this study was to assess the skin manifestations of TCS misuse over the face in the patients attending dermatology outpatient and to analyze various factors contributing to such misuse. Methods and Methods: A total of 200 patients with facial dermatoses using topical steroids over face for minimum period of 1 month, reported between June 2010 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…On the other hand, skin bleacher‐specific prevalences refer to the demographic characteristics of skin bleachers and hence apply specifically to skin bleaching practitioners (agents used, age groups, educational level, relationship/marital status, employment status, and residential area). In order to avoid potential inflation of population prevalences, studies presenting data on purposively sampled skin bleachers (lifetime prevalence ≈100%) were not included in estimating population prevalences. They were also omitted from the meta‐regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, skin bleacher‐specific prevalences refer to the demographic characteristics of skin bleachers and hence apply specifically to skin bleaching practitioners (agents used, age groups, educational level, relationship/marital status, employment status, and residential area). In order to avoid potential inflation of population prevalences, studies presenting data on purposively sampled skin bleachers (lifetime prevalence ≈100%) were not included in estimating population prevalences. They were also omitted from the meta‐regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6] Also, it's inappropriate use in the treatment of various dermatological disorders like acne, bacterial or fungal infections, and rash by non-registered practitioners or on the advice of pharmacist or chemist shops is a major concern. [7][8] This will increase the adverse effects and can lead to dependence on these medications. So, urgent steps are required to eliminate the root of this problem at the earliest.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In our study females' outnumbered males, this is in accordance with other studies. [10,11] In our study, maximum number of patients belonged to the age group of 11-20 years, while some studies shows 20-30 year age group more prone for TCS abuse . Acne was the most common indication of steroid application; hence, the predominance of younger age group in our study is easily explained and this is also reported in a study by Manchanda et al [12] Most of the subjects were using potent TCs in our study, which is in concordance with prior studies from other countries.…”
Section: Discussionmentioning
confidence: 99%